PENGARUH STRUKTUR CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (Media Riset Akuntansi, 2022)
The purpose of this study was to determine and analyze the effect of the proportion of independent commissioners, the frequency of board of commissioners' meetings, the size of the audit committee, and the frequency of audit committee meetings on firm value. The population of this study is the property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2015. The sampling technique used was purposive sampling method, in order to obtain as many as 63 samples. This study uses a descriptive analysis method using the SPSS 23 program. The results show that the proportion of independent commissioners, the frequency of board of commissioners' meetings, and the frequency of audit committee meetings have no effect on firm value. While the size of the audit committee has a significant effect on firm value. The results of this study are expected to contribute to the field of financial accounting.